PERANAN BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA ASN RSUD WALUYO JATI KRAKSAAN - Pratiwi, Diah Restu; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
In an organization, human resources are considered as an asset for organization because it has very important roles and functions for the success of the organization in achieving its goals. It is necessary to have Human Resource Management in achieving organizational goals. The purpose of this study was to analyze and examine the role of organizational culture and leadership style on job satisfaction through motivation as an intervening variable. The population in this study was the State Civil Apparatus of Public Hospital Waluyo Jati Kraksaan. The sampling technique used slovin’s formula. Data analysis and hypothesis testing in this study applied Partial Least Square Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis test using Smart PLS 3.0 application showed that organizational culture has a positive and significant effect on motivation, leadership style has a positive and significant effect on motivation, organizational culture has a positive but not significant effect on job satisfaction, leadership style has a positive and significant effect on Job satisfaction, motivation has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction through motivation, leadership style has a positive and significant effect on job satisfaction through motivation.